ANALISIS FAKTOR PENYEBAB KECELAKAAN KERJA DI PERTAMBANGAN - Roliana Harahap; Susilawati (CV. ADIBA AISHA AMIRA, 2023)
The mining industry is one of the industrial sectors that supports the national economy. The mining sector in Indonesia contributes a large proportion of state revenues starting from export earnings, regional development, increasing economic activity, opening up employment opportunities and sources of income to the central and regional budgets. 1 Work accidents are unplanned, uncontrollable and unwanted events (upplanned, uncontrolled and undesired) at work, which is caused either directly or indirectly, by unsafe actions and or unsafe conditions resulting in the cessation of work activities. This research is a systematic review (Systematic Review) using the PRISMA (Preferred Reporting Items for Systematic Review and Meta- analysis) method. The percentage of causes of work accidents was 100% due to education level, 67.67% working age, 47% working time, 77.78% OSH knowledge and 55.56% behavior not using personal protective equipment (PPE). The biggest factor causing accidents in the mining industry is the level of education, which is 100% and the smallest is caused by work age, which is 47%. Mining companies should conduct OSH training for workers who have just entered work and employees who are already working in their companies. Companies must evaluate the causes of accidents that occur and document every accident that occurs